(untitled) (Bangladesh Journal of Anatomy, 2021)
Context: Under the influence of hormones, ovary undergoes various changes especially in the volume of follicles as well as stroma. This change starts from prepubertal period and continue up to post-menopausal period. This repetitive growth and regression of ovarian follicles predispose to develop many abnormalities of ovarian structures and functions. This study is designed to evaluate the proportional volume of follicles and stroma in relation to different age groups. Materials & Methods: A cross sectional, descriptive type of study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to June 2011. The present study was performed on 24 postmortem right sided ovaries, age ranging from 5 to 65 years. The samples were divided into four different age groups. They were group A (5-12years), group B (13-45 years), group C (46-51 years) and group D (52-65years). The structural component was determined by Hennig’s method and calculation was done with the point counting technique. Results: The proportional volume of follicles and stroma were (67.50 ± 5.21)% & (32.50 ± 5.21)% in group A, 82.33 ± 3.83% & 17.67 ± 3.83% in group B, (70.00 ± 0.63)% & (30.00±0.63)% in group C and (24.50± 0.55)% & (75.50±0.55)% in group D. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 2, pp. 32-36